Densely Functionalized 2-Methylideneazetidines: Evaluation as Antibacterials - Giovanni Petrillo; Cinzia Tavani; Lara Bianchi; Alice Benzi; Maria Maddalena Cavalluzzi; Lara Salvagno; Laura Quintieri; Annalisa De Palma; Leonardo Caputo; Antonio Rosato; Giovanni Lentini (Molecules, 2021)
Twenty-two novel, variously substituted nitroazetidines were designed as both sulfonamide and urethane vinylogs possibly endowed with antimicrobial activity. The compounds under study were obtained following a general procedure recently developed, starting from 4-nitropentadienoates deriving from a common β-nitrothiophenic precursor. While being devoid of any activity against fungi and Gram-negative bacteria, most of the title compounds performed as potent antibacterial agents on Gram-positive bacteria (E. faecalis and three strains of S. aureus), with the most potent congener being the 1-(4-chlorobenzyl)-3-nitro-4-(p-tolyl)azetidine 22, which displayed potency close to that of norfloxacin, the reference antibiotic (minimum inhibitory concentration values 4 and 1–2 μg/mL, respectively). Since 22 combines a relatively efficient activity against Gram-positive bacteria and a cytotoxicity on eucharyotic cells only at 4-times higher concentrations (inhibiting concentration on 50% of the cultured eukaryotic cells: 36 ± 10 μM, MIC: 8.6 μM), it may be considered as a promising hit compound for the development of a new series of antibacterials selectively active on Gram-positive pathogens. The relatively concise synthetic route described herein, based on widely available starting materials, could feed further structure–activity relationship studies, thus allowing for the fine investigation and optimization of the toxico-pharmacological profile.